Relacionamento entre estrutura e função muscular periférica, inflamação sistêmica e regulação autonômica na capacidade funcional de adultos obesos com ou sem distúrbios metabólicos - Carvalho, Lívia Pinheiro (2017)
Obesity is considered a worldwide epidemic, exerting great impact on cardiometabolic morbidity and mortality. Obese individuals often present poor cardiorespiratory fitness (CRF), altered cardiac autonomic modulation (CAM) and muscle functioning and, therefore a higher risk of developing physical disabilities and life-threatening events later in life. However, a subpopulation, the so-called "metabolically healthy obese," appears to be less likely to develop such impairments because of a more favorable metabolic profile, despite excessive body fat. In this context, we proposed the accomplishment of three observational and cross-sectional studies that could contribute to the comprehension of the global capacity and physiological responses in young adults aged 20 to 45 years when submitted to different exercise tests, including the cardiopulmonary exercise testing (CPX), the gold standard method for evaluating CRF, and field functional tests, which are less costly and interesting because they mimic usual activities of daily living, such as the six-minute step test (6MST) (Study I) an the six-minute walking test (Study II). Thereafter (Studies II and III), we aimed to investigate whether there would be an influence of the metabolic profile, namely the association with Metabolic Syndrome (MetS), insulin resistance (IR) and systemic inflammation, in such clinical outcomes. The first study evaluated a sample composed only of sedentary normal-weight (NW) and obese (OB) women (n=31) to investigate the agreement between cardiorespiratory responses from the 6MST and CPX; to develop a predictive equation from the 6MST to estimate the maximal aerobic capacity (VO2peak in the CPX); and to investigate whether aerobic/functional capacities are related to muscle strength and power (knee extensor peak isokinetic/isometric torque, power and total work). We found that CRF, functional capacity (6MST), relative muscle strength and power were lower in OB than in NW women. We demonstrated that body mass index (BMI), age and performance (up-and-down cycles) in the 6MST explain 83% of maximal VO2peak total variance, and it was possible to elaborate the predictive equation. Moderate to strong correlations were found between CRF, functional capacity (6MST) and muscular strength and power. Study II (n=66) aimed at evaluating cardiorespiratory responses to exercise and CAM (at rest and during the submaximal six-minute walking test [6MWT] and 6MST) by linear and nonlinear indices of heart rate variability (HRV), and their associations with IR and systemic in NW and OB men and women, with or without MetS. We found that cardiorespiratory responses to exercise are affected by obesity per se and do not reflect the influence of MetS in obese patients. However, MetS seems to affect CAM at rest and in response to exercise, since we observed reduced parasympathetic modulation and overall HRV at rest as well as an altered complexity in response to exercise in the OB group with MetS. IR was associated with altered CRF, but not with HRV, and serum levels of IL-10 and TNF-α were associated with HRV. Finally, we demonstrated that the 6MST induces greater cardiovascular stress than the 6MWT, and may be applicable for MAC evaluation in clinical practice. Study III (n=61) aimed to compare the metabolic and inflammatory profile, especially the role of specific biomarkers (leptin, LP, adiponectin, ADP and myostatin, MSTN) and muscle function, energy expenditure and CRF between the same groups. The last group, however, was characterized by the association of MetS with IR. We concluded from this study that high levels of MSTN and LP-to-ADP ratio are associated with MetS and IR, low-grade chronic inflammation and low muscle mass. LP/ADP is associated with parameters of obesity alone and with CRF, and neither LP/ADP nor MSTN are associated with energy expenditure and muscle function, as suggested in previous studies in animal models.